PENINGKATAN KETERAMPILAN SOSIAL MELALUI KEGIATAN BERMAIN MENGGUNAKAN NYANYIAN - DIANA SETYANINGSIH (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2018)
Abstrac : the aims of this reseacrh is to get information and data about the effort to increase children’s social skills in group B5 kindergarten through play activities with the song in TK YPPK Bintang Kecil, Abepura, Jayapura City 2014, with 18 children. Reseacrh Method used action research method. This method condused in two ciycles according to kemmis and Taggart model which consist of 4 stages (plan, action, observation and reflection). The process of data collection using the interview notes, field notes, instrument monitoring and documentation of action. Analysis of data using qualitative analysis and quantitative analysis. Social skills children can be increased after the action through play activities using singing. It can be seen from the results of research that says that the average grade in the pre-action amounted to 49.30%. After the action in the first cycle increases the average grade was increased to 71.18% and the second cycle increased to 84.42%.